2007
DOI: 10.2106/jbjs.f.00955
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Delta-III Total Shoulder Replacement Combined with Latissimus Dorsi Transfer

Abstract: In the presence of severe loss of active elevation and external rotation, combined latissimus dorsi transfer and reverse total shoulder arthroplasty can restore elevation and external rotation, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 17 publications
2
80
1
2
Order By: Relevance
“…We found no significant functional deterioration over ten years, with the relative Reverse shoulder arthroplasty in younger patients 14 Constant score and SSV remaining above 70% and 60%, respectively at 2 to 5 years, 5 to 7 years and 7 to 10 years (Table 5).…”
Section: Clinical Resultsmentioning
confidence: 68%
“…We found no significant functional deterioration over ten years, with the relative Reverse shoulder arthroplasty in younger patients 14 Constant score and SSV remaining above 70% and 60%, respectively at 2 to 5 years, 5 to 7 years and 7 to 10 years (Table 5).…”
Section: Clinical Resultsmentioning
confidence: 68%
“…Review of the literature suggests the reported gain in active external rotation after an isolated transfer of the LD is modest, but patient satisfaction remains high because the arm is stabilized by the transfer [1,2,18,23,30,35,47]. Gerber [19] has recently reported a similar series of patients treated with a LD transfer and reverse shoulder arthroplasty; his preliminary results suggested similar promise but demonstrated a lower gain in external rotation. In addition, the isolated LD tendon is often thin and fragile while harvesting of both LD/TM tendons provides a strong tendon unit, improving the ease and strength of the reattachment on the posterolateral part of the humerus.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,16,[21][22][23]26 Rates of RTSA have increased exponentially over the past decade, 8,17 and RTSA now comprises approximately one-third of all glenohumeral arthroplasty procedures and roughly one-fourth of arthroplasty-treated proximal humerus fractures. 20 This success has resulted in the rapid expansion of RTSA indications and application.…”
mentioning
confidence: 99%